Time between vulnerability disclosures: A measure of software product vulnerability. Issue 62 (September 2016) - Johnson, Pontus; Gorton, Dan; Lagerström, Robert; Ekstedt, Mathias
Abstract: Time between vulnerability disclosure (TBVD) for individual analysts is proposed as a meaningful measure of the likelihood of finding a zero-day vulnerability within a given timeframe. Based on publicly available data, probabilistic estimates of the TBVD of various software products are provided. Sixty-nine thousand six hundred forty-six vulnerabilities from the National Vulnerability Database (NVD) and the SecurityFocus Vulnerability Database were harvested, integrated and categorized according to the analysts responsible for their disclosure as well as by the affected software products. Probability distributions were fitted to the TBVD per analyst and product. Among competing distributions, the Gamma distribution demonstrated the best fit, with the shape parameter, k, similar for most products and analysts, while the scale parameter, θ, differed significantly. For forecasting, autoregressive models of the first order were fitted to the TBVD time series for various products. Evaluation demonstrated that forecasting of TBVD on a per product basis was feasible. Products were also characterized by their relative susceptibility to vulnerabilities with impact on confidentiality, integrity and availability respectively. The differences in TBVD between products is significant, e.g. spanning differences of over 500% among the 20 most common software products in our data. Differences are further accentuated by the differing impact, so that, e.g., the mean working time between disclosure of vulnerabilities with a complete impact on integrity (as defined by the Common Vulnerability Scoring System) for Linux (110 days) exceeds that of Windows 7 (6 days) by over 18 times.